Building Positive Organizations: A Typology of Positive Psychology Interventions - van Woerkom, Marianne (Frontiers in Psychology, 2021)
Research indicates that Positive Psychology Interventions (PPIs) in the work context have a small positive impact on improving desirable work outcomes, and a small to moderate effect on reducing undesirable work outcomes, suggesting that the effects of PPIs are not trivial, but also not large. Whereas this may be related to the difficulty of changing oneself or one's happiness levels, the relatively small effects of PPIs may also be due to the predominant use of one-off interventions instead of more structural interventions that reflect policy level commitment. Furthermore, since most PPIs tend to focus on the individual, one could question the long-term effectiveness of such interventions, especially when the work environment remains unchanged. In this paper, I introduce a typology of PPIs in organizations (TYPPIO) by distinguishing between the organizational level they target (the individual or group level), and between one-off and structural interventions. I argue that different types of interventions can strengthen each other, and that in order to make a sustainable contribution to the optimal functioning of workers, PPIs need to comprise a wide variety of one-off and structural interventions targeting both individuals and groups in organizations. Furthermore, I make suggestions for improving the long-term effectiveness of PPIs by drawing on the literature on transfer of training, nudging, and positive design.